2016
DOI: 10.1074/jbc.m115.695809
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of Interleukin 1β (IL-1β) Expression by Anthrax Lethal Toxin (LeTx) Is Reversed by Histone Deacetylase 8 (HDAC8) Inhibition in Murine Macrophages

Abstract: Many pathogenic microbes often release toxins that subvert the host's immune responses to render the environment suitable for their survival and proliferation. LeTx is one of the toxins causing immune paralysis by cleaving and inactivating the mitogen-activated protein kinase (MAPK) kinases (MEKs). Here, we show that inhibition of the histone deacetylase 8 (HDAC8) by either the HDAC8-specific inhibitor PCI-34051 or small interference (si)RNAs rendered LeTx-exposed murine macrophages responsive to LPS in pro-IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 90 publications
(86 reference statements)
0
17
0
Order By: Relevance
“…We previously showed that LeTx or HDAC8 overexpression leads to H3K27Ac deacetylation in murine macrophages [22,28]. Since the levels of H3K27Ac and H3K27me3 are inversely correlated, and an increase of H3K27me3 leads to down-regulation of PTEN expression [29,30,31,32], we examined both acetylation and methylation levels of H3K27.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed that LeTx or HDAC8 overexpression leads to H3K27Ac deacetylation in murine macrophages [22,28]. Since the levels of H3K27Ac and H3K27me3 are inversely correlated, and an increase of H3K27me3 leads to down-regulation of PTEN expression [29,30,31,32], we examined both acetylation and methylation levels of H3K27.…”
Section: Resultsmentioning
confidence: 99%
“…It is also known that H3K27 acetylation is mutually exclusive to methylation of the residue and H3K27 deacetylation is a prerequisite chromatin context for PRC2 to be active on histones [29,30,31]. In murine macrophages, we showed that LeTx suppresses gene transcription in part through up-regulating HDAC8 that leads to H3K27 deacetylation [23,28]. As expected, LeTx also induced HDAC8 mRNA expression, decreased H3K27Ac levels and increased H3K27me3 levels over 3 days in THP-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al reported that the HDAC8 inhibitor ITF3056 attenuated TNF-α and IL-1β production without a significant decrease in the IL-1β mRNA levels in vitro [ 27 ]. However, another study described that HDAC8 could suppress IL-1β production, leading to the hypoacetylation of histone H3K27 located on the pro-IL-1β enhancer and promoter regions in macrophages, such function that could be reversed by the HDAC8 inhibitor PCI-34051 to increase IL-1β production [ 49 ]. Consistently, the function of WK2-16 on IL-1β production is similar to PCI-34051.…”
Section: Discussionmentioning
confidence: 99%
“…There is a trend indicating increased Arg-1 expression after treatment with 10 µM PCI-34051, although, owing to high variation, this trend does not reach statistical significance. Previous studies have shown effects of PCI-34051 on mitochondrial cell death genes and IL-1β expression in lower concentrations (20 nM and 100 nM) on toxin-induced resistant RAW264.7 macrophages [ 43 , 44 ]. In addition, PCI-34051 was found to be neuroprotective in concentrations between 1 µM and 10 µM.…”
Section: Discussionmentioning
confidence: 99%